A Lipopolysaccharide O-Antigen Synthesis Gene in Mesorhizobium huakuii Plays Differentiated Roles in Root Nodule Symbiotic Compatibility with Astragalus sinicus - Tang, Zhide; Cai, Shuyun; Liu, Yuan; Li, Dongzhi; Xie, Fuli; Lin, Hui; Chen, Dasong; Li, Youguo (Molecular plant-microbe interactions, 2023)
Lipopolysaccharide (LPS) is a ubiquitous microbial-associated molecular pattern. Plants can sense the three components of LPS, including core polysaccharide, lipid A, and O-antigen. LPS biosynthesis is an essential factor for the successful establishment of symbiosis in the rhizobium–legume plant system. The MCHK_1752 gene ( Mesorhizobium huakuii 7653R gene) encodes O-antigen polymerase and affects the synthesis of O-antigen. Here, we investigated the symbiotic phenotypes of six Astragalus sinicus accessions inoculated with the MCHK_1752 deletion mutant strain. The results revealed that the MCHK_1752 deletion mutant strain had a suppressing effect on the symbiotic nitrogen fixation of two A. sinicus accessions, a promoting effect in three A. sinicus accessions, and no significant effect in one A. sinicus accessions. In addition, the effect of MCHK_1752 on the phenotype was confirmed by its complementary strains and LPS exogenous application. Deletion of MCHK_1752 showed no effect on the growth of a strain, but affected biofilm formation and led to higher susceptibility to stress in a strain. At the early symbiotic stage, Xinzi formed more infection threads and nodule primordia than Shengzhong under inoculation with the mutant, which might be an important reason for the final symbiotic phenotype. A comparison of early transcriptome data between Xinzi and Shengzhong also confirmed the phenotype at the early symbiotic stage. Our results suggest that O-antigen synthesis genes influence symbiotic compatibility during symbiotic nitrogen fixation. [Formula: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .